A nucleotide variant in the promoter region of the interleukin-6 gene associated with decreased bone mineral density - Ota, N.; Nakajima, T.; Nakazawa, I.; Suzuki, T.; Hosoi, T.; Orimo, H.; Inoue, S.; Shirai, Y.; Emi, M. (Journal of human genetics, 2001)
Interleukin-6 (IL6) has come to be regarded as a potential osteoporotic factor because it has stimulatory effects on cells of the osteoclast lineage, and, thus, may play a role in the pathogenesis of bone loss associated with estrogen deficiency. We previously described association of the IL6 microsatellite with bone mineral density (BMD), as well as genetic linkage of the IL6 locus to human osteoporosis, by means of sib-pair analysis. However, the molecular mechanism by which this locus regulates BMD remains unknown. Accordingly, we searched for polymorphisms in the 5′ and 3′ flanking regions and in all five exons of the IL6 gene in a Japanese population sample. We identified three single-nucleotide sequence variations: a C/G substitution at nucleotide (nt) −634 in the promoter region, a G/A substitution at nt 4391 in the 3′ noncoding region, and a variation in the AnTn tract around nt −447. The last of these had already been observed in Caucasians, as well as in Japanese. The single-nucleotide polymorphism at −634 created a restriction site for the Bsr BI endonuclease, and the frequency of the minor (G) allele was 0.184. Five haplotypes were constructed among three variations examined in the population. Linkage disequilibrium was observed between the variation at −634 and the variation at 4391, as well as between the variation at −634 and the AnTn tract variation. We found a significant correlation, in 470 subjects, between the presence of the G allele and decreased BMD, by analysis of variance. When BMD values were compared among the three genotypic groups (G/G, G/C, C/C) at nt −634, BMD was lowest among the G/G homozygotes (mean ± SD; 0.284 ± 0.062 g/cm 2 ), highest among the C/C homozygotes (0.314 ± 0.059 g/cm 2 ), and intermediate among the heterozygotes (0.303 ± 0.066 g/cm 2 ; P < 0.05).Given the several lines of evidence from different genetic studies, we suggest that IL6 is, indeed, one of the genes affecting bone metabolism, in which variations can lead to osteoporosis.